KING FEATURES SYNDICATE; TI, TOBACCO INST; TOBACCO MUSEUM OF NC; TOBACCO OBSERVER - ABRAMS,A; EBERLY,P; FLEMING,AT; GILMORE,TV (Tufts Archival Research Center, 2007)
Issue of the Tobacco Observer, a newsletter with a series of articles relating to issues regarding tobacco. Includes articles on smokers' rights, cigarette taxes, secondhand smoke and smoking on airplanes.